CT SCAN EVALUATION OF BLUNT ABDOMINAL TRAUMA PATIENTS IN EMERGENCY DEPARTMENT - Dr. Hemat Jangid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Blunt abdominal trauma represents a significant clinical challenge in emergency medicine, requiring rapid and accurate diagnosis to identify life-threatening injuries. Computed tomography (CT) scanning has emerged as the primary diagnostic modality for hemodynamically stable trauma patients, though its diagnostic accuracy and clinical utility require ongoing evaluation in diverse healthcare settings. Methods: A prospective observational study was conducted at Mahaveer Institute of Medical Science and Research from July to December 2023. Consecutive adult patients presenting with blunt abdominal trauma underwent standardized CT examination with intravenous contrast. CT findings were correlated with surgical outcomes, clinical management decisions, and patient outcomes. Diagnostic accuracy parameters including sensitivity, specificity, positive and negative predictive values were calculated using surgical findings and clinical outcomes as reference standards. Subgroup analyses were performed based on injury mechanism, patient demographics, and injury severity. Results: Among 350 enrolled patients, CT detected significant injuries in 234 cases (66.9%). Motor vehicle accidents represented the most common mechanism (56.6%), with liver injuries being most frequent (25.4%). CT demonstrated excellent diagnostic performance with sensitivity of 91.7% (95% CI: 87.2-95.1%), specificity of 73.1% (95% CI: 65.0-80.4%), positive predictive value of 84.6%, negative predictive value of 84.5%, and overall accuracy of 84.6%. CT-positive patients had significantly higher rates of surgical intervention (57.3% vs 5.2%, p<0.001), ICU admission (38.0% vs 10.3%, p<0.001), and longer hospital stays (4.8 vs 2.1 days, p<0.001). Active bleeding was identified in 9.7% of patients, guiding immediate intervention decisions. Conservative management was successful in 94.8% of CT-negative patients. Conclusion: CT scanning demonstrates excellent diagnostic accuracy for detecting significant blunt abdominal trauma injuries and strongly influences clinical decision-making. The high sensitivity and negative predictive value support its role as the primary diagnostic modality for hemodynamically stable trauma patients, enabling appropriate triage and resource allocation in emergency departments.